KUPRATLAR PARDALARIDA POLARON MASSASI: PARDA QALINLIGI SAMARASI - Gʻ.Xajibayev, D.; Ya.Yavidov, B. (SCIENCE and SOCIETY, 2023)
In this article the polarons of La2-xSrxCuO4 films grown on LaSrAlO4 and SrTiO3 substrates is considered. In particular, a dependence of polaron’s mass on the thickness of La2-xSrxCuO4 films is studied. It is shown that polaron’s mass depend on the film’s thickness in both adiabatic and nonadiabatic limits. It is established that upon decreasing the film’s thickness the mass of polaron decreases in LSCO/LSAO system and incraeses in LSCO/STO system in both adiabatic and nonadiabatic limits.
Keywords: cuprates; films; film’s thickness; small polaron; polaron’s mass